THE INFLUENCE OF INTERMITTENT COMPRESSION THERAPY USING SPHGYMOMANOMETER ON PRESSURE CHANGES AND WALKING ABILITY ON INDIVIDUALS AFFECTED WITH PERIPHERAL ARTERIAL DISEASES OF LOWER LIMBS (International Journal of Physiotherapy, 2016)
Background: To find out the influence of intermittent compression therapy using sphygmomanometer on pressure changes and walking ability on individuals affected with peripheral arterial diseases of lower limbs.Methods: Total thirty patients’ age 30 to 70 years post peripheral arterial diseases individuals included for study. These patients were randomly allocated to intervention group (n=15), which underwent a 6- weeks training program & control group (n=15) that received standard care and unsupervised exercise protocol. Primary outcome was change in ABI levels as determined in before and after the intervention program. Secondary outcomes were intermittent claudicating distance and walking capacity as assessed by the walking impairment questionnaire.Results: Paired sample t- test was used to analyze changes from before and after intervention program. There is a statistically significant (p=0.000) improvement in both experimental group and control group but when compared to control group, experimental group shows improvement in the mean values in all parameters.Conclusion: In this study the Ankle Brachial Index (ABI), Intermittent Claudication Distance (ICD) and Walking Impairment Questionnaire (WIQ) improved significantly in experimental group than control group by applying the pneumatic compression therapy with the sphygmomanometer and graded walking exercise. Hence, the study recommends that intermittent pneumatic therapy along with graded exercise is most effective in improving Ankle Brachial Index (ABI), Intermittent Claudication Distance (ICD) and Walking capacity in PAD individuals.